Social Representations: The Meaning of "Physical Education" for Students of the Subject [Representaciones Sociales: El Significado de la Educación Física Para Los Estudiantes de Esa Disciplina] - Riquelme-Uribe, D (Universidad Autonoma de Baja California, 2018)
This subject sought to analyze Chilean physical education students social representations by exploring what physical education means to them. A non-experimental, cross-sectional and mixed-method design was used. The sample was made up of 200 students from the pedagogy in physical education degree in 12 Chilean universities, who were selected under purposive non-probability criteria. The results show that the defining words with the greatest semantic weight are "health", "sport", "motor skills", and "movement". The study concludes that social representations in this field are linked to health and well-being, and relate to movement and the study of human motor skills, providing pedagogical value through aspects such as physical activity, recreation, and sport.